Capital Market Development, International Integration, Legal Systems, and the Value of Corporate Diversification: A Cross-Country Analysis - Fauver, Larry; Houston, Joel; Naranjo, Andy (Journal of Financial and Quantitative Analysis, 2003)
Larry Fauver, Joel Houston, Andy Naranjo, Capital Market Development, International Integration, Legal Systems, and the Value of Corporate Diversification: A Cross-Country Analysis, The Journal of Financial and Quantitative Analysis, Vol. 38, No. 1 (Mar., 2003), pp. 135-157